Inside Back Cover: Influence of Alcohol β‐Fluorination on Hydrogen‐Bond Acidity of Conformationally Flexible Substrates (Chem. Eur. J. 12/2017). Issue 12 (27th December 2016) - Graton, Jerome; Compain, Guillaume; Besseau, Francois; Bogdan, Elena; Watts, Joseph M.; Mtashobya, Lewis; Wang, Zhong; Weymouth‐Wilson, Alex; Galland, Nicolas; Le Questel, Jean‐Yves; Linclau, Bruno
Abstract : Fluorination induces significant modulations of molecular properties. The focus herein is on quantifying its influence on the hydrogen‐bond (H‐bond) donating capacity of a vicinal OH group. Using β‐fluorohydrin probes, changes in H‐bond acidity are rationalized by subtle differences in the conformational landscape. The OH⋅⋅⋅F intramolecular H‐bonds form five‐membered rings, symbolized here by the "Anneaux de Buren" (Nantes, France), and imply a decrease of the OH H‐bond acidity in monofluorinated compounds. In contrast, di‐ and trifluorination of β‐fluorohydrins lead to a successive increase of H‐bond acidity. More information can be found in the Full Paper by J. Graton, J.‐Y. Le Questel, B. Linclau et al. onpage 2811 ff.